Performance Measurement Systems for Supply Chain Management: How to Manage Its Maturity - Guilherme Francisco Frederico; Roberto Antonio Martins (International Journal of Supply Chain Management, 2014)
Supply chains have gained important focus after 2000s due to not only the opportunities that it can provide but also the complexity involved on its management. Into this context, the implementation of different management practices can help companies to achieve better performance in their supply chains. As part of these practices it can be considered the Performance Measurement System (PMS). The theory for PMS has been concentrated on only organization perspective. At the same time the theory about PMS for SCM is focused more on scope of measurementleaving a lack with regards other dimensions that must be considered on the PMS maturity development. Therefore, this paper aims to present the findings from the literature review about PMS for SCM and maturity of PMS. As contribution an theoretical model is proposed to help practitioners and researchers on the maturity management of PMSs for SCM.